Könlösa akademiker och maskulina arbetare: En diskussion kring genusperspektiv och arbetarklassforskning - Eldh, Christer (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1993)
The present article discusses sexual consciousness in the field of research on the working class. By way of a re-reading of Billy Ehn's study of factory life in Arbetets flytande gränser, the academic's own masculinity is contrasted with the masculinity which asserts itself in the factory. By employing a gender perspective and reflecting on the type of masculinity taken for granted by intellectuals and members of the working class, respectively, we are able to perceive how unconscious sexual conceptions influence scholarly interpretation.